Frontal knee alignment influences the vertical orientation of the femoral neck in standing position. (1st December 2021) - Ahmad, Sufian S.; Weinrich, Luise; Giebel, Gregor M.; Beyer, Myriam R.; Stöckle, Ulrich; Konrads, Christian
Abstract : Aims: The aim of this study was to determine the association between knee alignment and the vertical orientation of the femoral neck in relation to the floor. This could be clinically important because changes of femoral neck orientation might alter chondral joint contact zones and joint reaction forces, potentially inducing problems like pain in pre-existing chondral degeneration. Further, the femoral neck orientation influences the ischiofemoral space and a small ischiofemoral distance can lead to impingement. We hypothesized that a valgus knee alignment is associated with a more vertical orientation of the femoral neck in standing position, compared to a varus knee. We further hypothesized that realignment surgery around the knee alters the vertical orientation of the femoral neck. Methods: Long-leg standing radiographs of patients undergoing realignment surgery around the knee were used. The hip-knee-ankle angle (HKA) and the vertical orientation of the femoral neck in relation to the floor were measured, prior to surgery and after osteotomy-site-union. Linear regression was performed to determine the influence of knee alignment on the vertical orientation of the femoral neck. Results: The cohort included 147 patients who underwent knee realignment-surgery. The mean age was 51.5 years (SD 11). Overall, 106 patients underwent a valgisation-osteotomy, while 41 underwent varisation osteotomy. There was a significant association between the orientation of the knee and the coronal neck-orientation. In the varus group, the median orientation of the femoral neck was 46.5° (interquartile range (IQR) 49.7° to 50.0°), while in the valgus group, the orientation was 52.0° (IQR 46.5° to 56.7°; p < 0.001). Linear regression analysis revealed that HKA demonstrated a direct influence on the coronal neck-orientation ( β = 0.5 (95% confidence interval (CI) 0.2 to 0.7); p = 0.002). Linear regression also showed that realignment surgery was associated with a significant influence on the change in the coronal femoral neck orientation ( β = 5.6 (95% CI 1.5 to 9.8); p = 0.008). Conclusion: Varus or valgus knee alignment is associated with either a more horizontal or a more vertical femoral neck orientation in standing position, respectively. Subsequently, osteotomies around the knee alter the vertical orientation of the femoral neck. These aspects are of importance when planning osteotomies around the knee in order to appreciate the effects on the adjacent hip joint. The concept may be of even more relevance in dysplastic hips. Cite this article: Bone Jt Open  2021;2(12):1057–1061.